Relationship between Socio-economic Characteristics and Husband Support with Inclusive Antenatal Care (ANC) at South Denpasar Health Centre III - Mira Kristiani Dewi; Widarini; I Nyoman Mangku Karmaya (Universitas Udayana, 2014)
Background and purpose: Maternal mortality is one of indicators within the millennium development goals. In Indonesia, the first point of entry for maternal health care is through midwives working from health centres. Comprehensive antenatal care is extremely important in order to ensure a healthy and natural pregnancy. This study explored the relationship between socio-economic characteristics and the support of husband with inclusive antenatal care in South Denpasar III Community Health Centre. Methods: This study was cross-sectional using a quantitative approach among sixty nine espondents whom were selected using simple random sampling. Data was collected guided questionnaires and secondary data was obtained through clinic records. Data was processed using univariate, bivariate (chi-squared test) and multivariate (logistic regression) analysis. Results: Results indicated that there is a relationship between knowledge (p=0.045), attitude (p=0.039), education (p=0.007), income (p=0.013) and husband support (p=0.011) with the regularity of antenatal care access by expectant mothers. Whereas age, parity and occupation were not influential factors. Conclusion: Husband support plays the most dominant role in influencing the inclusivity of maternal antenatal care.